2021
DOI: 10.3390/en14040998
|View full text |Cite
|
Sign up to set email alerts
|

A Heating Controller Designing Based on Living Space Heating Dynamic’s Model Approach in a Smart Building

Abstract: Most already advanced developed heating control systems remain either in a prototype state (because of their relatively complex implementation requirements) or require very specific technologies not implementable in most existing buildings. On the other hand, the above-mentioned analysis has also pointed out that most smart building energy management systems deploy quite very basic heating control strategies limited to quite simplistic predesigned use-case scenarios. In the present paper, we propose a heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to the authors, this solution provides safety, positively influences costs, and increases efficiency, performance, and useability. The authors of the paper [22] propose a different strategy of heating control, emphasizing the integration of user presence as an additional factor in managing heating within the living space. They present a flexible heating control system that adapts to diverse occupants within the heating network.…”
Section: Heating and Coolingmentioning
confidence: 99%
“…According to the authors, this solution provides safety, positively influences costs, and increases efficiency, performance, and useability. The authors of the paper [22] propose a different strategy of heating control, emphasizing the integration of user presence as an additional factor in managing heating within the living space. They present a flexible heating control system that adapts to diverse occupants within the heating network.…”
Section: Heating and Coolingmentioning
confidence: 99%
“…Another important aspect is the location of the building in relation to world directions and the density of buildings in the surroundings [11][12][13][14]. Scientific studies have shown that the operating habits and routine of residents with respect to their temperature preferences also have a significant impact on the heat demand [15][16][17]. The energy efficiency of a building depends not only on the structure of the building itself, but also on the behavior of its inhabitants.…”
Section: Introductionmentioning
confidence: 99%